2018
DOI: 10.3233/cbm-171156
|View full text |Cite
|
Sign up to set email alerts
|

Studying the frequency of aberrant DNA methylation of APC, P14, and E-cadherin genes in HCV-related hepatocarcinogenesis

Abstract: Aberrant DNA methylation of multiple genes is associated with disease progression in HCV related cirrhosis. Moreover, early detection of promotor methylation of these may sever as good biomarker for early detection and therapeutic targets in high risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Differential methylation was observed at CpGs associated with P14 and RASSF1A , previously shown to be aberrantly methylated in HCC (Fig. B) [51–53]. In the CLD samples, we detected 586 DM CpGs compared with normal liver (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Differential methylation was observed at CpGs associated with P14 and RASSF1A , previously shown to be aberrantly methylated in HCC (Fig. B) [51–53]. In the CLD samples, we detected 586 DM CpGs compared with normal liver (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…60 For example, HCV induces epigenetic modifications that can result in genome instability due to global hypomethylation, releasing suppression of oncogenes such as HRAS, KRAS and NRAS, as well as silencing of tumour suppressor genes such as APC, P14 and E-cadherin via hypermethylation. 59,61 Therefore, delayed treatment of known HCV infection represents a worst-case cost scenario, in which the high costs of DAA therapy do not offset the potentially much higher costs of treatment for cirrhosis or HCC. It is not necessary just to treat HCV infection; it is necessary to do so promptly.…”
Section: Long -Term Cos Ts and Ris K Smentioning
confidence: 99%
“…The proliferative pathways and epigenetic changes induced during long‐term HCV infection are not necessarily restored to the pre‐HCV state even when the virus is eliminated, indicating that some effects of HCV infection are irreversible 60 . For example, HCV induces epigenetic modifications that can result in genome instability due to global hypomethylation, releasing suppression of oncogenes such as HRAS, KRAS and NRAS, as well as silencing of tumour suppressor genes such as APC, P14 and E‐cadherin via hypermethylation 59,61 . Therefore, delayed treatment of known HCV infection represents a worst‐case cost scenario, in which the high costs of DAA therapy do not offset the potentially much higher costs of treatment for cirrhosis or HCC.…”
Section: Long‐term Costs and Risksmentioning
confidence: 99%
“…Several studies have shown that DNA hypermethylation in cancer cells targets tumor suppressor genes explicitly, resulting in growth selection and uncontrolled cell proliferation [25,26,27,28]. Many tumor suppressor genes are inactivated by this mechanism in cancer such as the adenomatous polyposis coli (APC) [29], retinoblastoma (Rb) [30], Von Hippel-Lindau (VHL), BRCA1 [31], and several other genes that are involved in DNA repair (MGMT; O-6-Methylguanine-DNA Methyltransferase), cell cycle progression (p16 INK4a , p15 INK4b ), apoptosis (DAPK; death-associated protein kinase-1), or antioxidation (GSTP1; Glutathione S-Transferase P-1) [32]. The extent to which DNA de novo methylation contributes to cancer development and progression varies among different types of cancer; very high in colon cancer, while rare in brain tumors [33].…”
Section: Dna Methylation In Cancermentioning
confidence: 99%